Farmers perceptions of crop pests and pest control practices in rainfed cowpea cropping systems in Kano, Nigeria - Bottenberg, H. (Informa UK Limited, 1995)
Farmers of rainfed cowpea/groundnut/millet/sorghum cropping systems in Kano, Nigeria, ranked arthropods as the major production constraint in cowpea and groundnut in 1991 and 1992. At least 25% of the farmers also reported severe infestations by Striga gesneroides a parasitic weed of cowpea. Drought was regarded as the major constraint in millet and sorghum. Farmers reported a total of 19 arthropod species, of which 10 occurred on two or more crops, five exclusively on cowpea, two on groundnut and two on sorghum. In an identification test of common phytophagous arthropods, farmers used specific names for aphids and podsucking bugs but more variable, descriptive names for flower thrips, pod borers and bruchids. More than half the farmers (57.5%) correctly identified the feeding site and host plant of the arthropods. Despite the high level of pest awareness, the majority of farmers did not practice any type of pest control. Less than 15% used chemical insecticides primarily because of their high cost and lack of availability. Traditional control was practised by less than 11% of the farmers and was limited to manual removal of pests, beating with branches, and sprinkling ashes or manure with or without kerosene or petrol on the crop.